Are Household Potato Frying Habits Suitable for Preventing Acrylamide Exposure? - Marta Mesias; Cristina Delgado-Andrade; Francisco J. Morales (Foods, 2020)
A survey was conducted of 730 Spanish households to identify culinary practices which might influence acrylamide formation during the domestic preparation of french fries and their compliance with the acrylamide mitigation strategies described in the 2017/2158 Regulation. Spanish household practices conformed with the majority of recommendations for the selection, storing and handling of potatoes, with the exception of soaking potato strips. Olive oil was the preferred frying oil (78.7%) and frying pans were the most common kitchen utensils used for frying (79.0%), leading to a higher oil replacement rate than with a deep-fryer. Although frying temperature was usually controlled (81.0%), participants were unaware of the maximum temperature recommended for preventing acrylamide formation. For french fries, color was the main criteria when deciding the end-point of frying (85.3%). Although a golden color was preferred by respondents (87.3%), color guidelines are recommended in order to unify the definition of “golden.” The results conclude that habits of the Spanish population are in line with recommendations to mitigate acrylamide during french fry preparation. Furthermore, these habits do not include practices that risk increasing acrylamide formation. Nevertheless, educational initiatives tailored towards consumers would reduce the formation of this contaminant and, consequently, exposure to it in a domestic setting.